FUNCTIONAL CONDITION OF KIDNEYS IN PATIENTS WITH ARTERIAL HYPERTENSION IN COMBINATION WITH TYPE 2 DIABETES MELLITUS - Bilovol, O.M.; Kniazkova, I.I.; Kirienko, O.M.; Kuzminova, N.V.; Golovachova, V.O.; Kirienko, D.O.; Abramova, L.P. (World of Medicine and Biology, 2022)
The purpose of the study was to clarify the diagnostic significance of neutrophil gelatinase-associated lipocalin and cystatin C in the blood of patients with arterial hypertension and type 2 diabetes mellitus and their correlation with intrarenal hemodynamic parameters. It was installed that in comparison with persons without diabetes in patients with arterial hypertension and type 2 diabetes mellitus at the stage of preclinical kidney damage found a more significant increase in neutrophil gelatinase-associated lipocalin and cystatin C in the blood. This allows us to consider these indicators as diagnostic manifestations of early detection of diabetic nephropathy. It was determined that a significant decrease in the final diastolic arterial blood flow velocities and a significant increase in the resistance index are diagnostic markers of morpho-functional changes in the kidneys during duplex scanning of the renal arteries in patients with arterial hypertension and type 2 diabetes mellitus.
Keywords: neutrophil gelatinase-associated lipocalin; cystatin C; duplex scanning of renal arteries; arterial hypertension; type 2 diabetes mellitus